Modernization of operating chicory factories using continuous pulsating extractors - D. P. Iovlev; M. I. Farakhov; R. R. Akberov; I. R. Stekolshchikov; A. V. Akhmerov (Новые технологии, 2022)
Chicory roots are a valuable source of inulin and other healthy nutrients. The most common direction of their industrial processing is instant chicory powder production. Extraction is the main process in the production. Conventional extraction methods, which include maceration, percolation and extraction in a screw extractor, have a number of significant drawbacks, including high capital and operating costs, low quality of the resulting extract, complexity in repairing equipment, short overhaul life, etc. The purpose of the present study was to assess the technical feasibility of increasing extraction process efficiency through using continuous pulsating extractors (CPE) developed by the Ingehim company, in which a non-stationary, countercurrent mode of interaction of raw materials with the extractant is incorporated. Testing of engineering solutions implemented in CPE was carried out at a pilot pulsating unit (PPU). For extraction, roasted and crushed (5–20 mm) chicory roots from one of the operating chicory factories were used. The ratio chicory : water during extraction was 1 : 4.5, which is 1.5–2.5 times lower than in conventional extractors. A lower extraction temperature (up to 85°C) combined with a shorter extraction time (up to 1 hour) may help retain more inulin and other nutrients as compared to conventional methods. The results of the study at the PPU under these conditions confirmed the high yield of water-soluble solids (up to 98%) without additional grinding. A scheme for the modernization of a chicory factory equipped with the most common percolation extraction equipment having a feed capacity of 400 kg/h is proposed through using CPE. 3D images of the proposed modernization are shown. A comparative assessment of energy consumption for extraction using different methods is given. The results of the study indicate the capability and high efficiency of CPE for extracting chicory, which is confirmed by a decrease of up to 3.6 times in the total specific energy consumption for obtaining 1 kg of instant chicory powder compared to conventional extractors. Low capital and operating costs determine the prospects for using CPE for the modernization of existing chicory factories or the creation of new energy-efficient factories.